2006
DOI: 10.1021/ie050160p
|View full text |Cite
|
Sign up to set email alerts
|

Equilibria in Limestone-Based FGD Process:  Magnesium Addition

Abstract: On the basis of chemical equilibria, the model of sulfur dioxide solubility in solutions applied in FGD (flue gas desulfurization) systems with magnesium salts addition is developed. The influence of magnesium chloride or magnesium sulfate on solution ability to absorb SO 2 , pH, ions concentration, and calcium salts solubility is presented. The mechanisms leading to a decrease of calcium carbonate solubility and/or to limestone particle blinding caused by magnesium salts addition are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Flue gas desulfurization (FGD) is recognized as the most effective technology for removing SO 2 emissions derived from fossil-fuel combustion and metallurgical and oil-refining industries. In turn, wet FGD using Ca-based slurries as absorbents (limestone and lime) is the most widely applied method because of the abundance of the components, the reliability of the system, and the well-known chemistry that takes place during the process. The literature has already highlighted the virtues of substituting lime and limestone with magnesium compounds because of the greater solubility of magnesium sulfite/sulfate products with respect to their calcium equivalents. This fact allows maintaining an alkaline pH during longer periods of desulfurization and hence results in an improved SO 2 removal efficiency. However, although this enhancement effect is widely known, the higher costs of magnesium compounds has resulted in only slight additions (3–8 wt %) to the Ca-based conventional methods, modifying them to become magnesium-enhanced limestone/lime processes. , Fostered by the Industrial Emissions Directive of the European Union (2010/75/EU) and the 2013 Best Available Techniques (BAT) reference documents, the potential reutilization of residues as desulfurization agents have been the topic of several researches. ,, In this regard, the authors have reported that the reutilization of several byproducts from the calcination of natural magnesite is a feasible technology that can attain a 100% removal efficiency by fully making profit of the magnesium enhancement effect . By this manner, a sustainable closed-loop processin which the byproducts from the SO 2 emission process itself are reused as absorbentscould be adapted to the overall production process, following the guidelines of legislation and economic optimization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flue gas desulfurization (FGD) is recognized as the most effective technology for removing SO 2 emissions derived from fossil-fuel combustion and metallurgical and oil-refining industries. In turn, wet FGD using Ca-based slurries as absorbents (limestone and lime) is the most widely applied method because of the abundance of the components, the reliability of the system, and the well-known chemistry that takes place during the process. The literature has already highlighted the virtues of substituting lime and limestone with magnesium compounds because of the greater solubility of magnesium sulfite/sulfate products with respect to their calcium equivalents. This fact allows maintaining an alkaline pH during longer periods of desulfurization and hence results in an improved SO 2 removal efficiency. However, although this enhancement effect is widely known, the higher costs of magnesium compounds has resulted in only slight additions (3–8 wt %) to the Ca-based conventional methods, modifying them to become magnesium-enhanced limestone/lime processes. , Fostered by the Industrial Emissions Directive of the European Union (2010/75/EU) and the 2013 Best Available Techniques (BAT) reference documents, the potential reutilization of residues as desulfurization agents have been the topic of several researches. ,, In this regard, the authors have reported that the reutilization of several byproducts from the calcination of natural magnesite is a feasible technology that can attain a 100% removal efficiency by fully making profit of the magnesium enhancement effect . By this manner, a sustainable closed-loop processin which the byproducts from the SO 2 emission process itself are reused as absorbentscould be adapted to the overall production process, following the guidelines of legislation and economic optimization.…”
Section: Introductionmentioning
confidence: 99%
“…However, although this enhancement effect is widely known, the higher costs of magnesium compounds has resulted in only slight additions (3−8 wt %) to the Ca-based conventional methods, modifying them to become magnesium-enhanced limestone/ lime processes. 12,13 Fostered by the Industrial Emissions Directive of the European Union (2010/75/EU) and the 2013 Best Available Techniques (BAT) reference documents, the potential reutilization of residues as desulfurization agents have been the topic of several researches. 10,11,14 In this regard, the authors have reported that the reutilization of several byproducts from the calcination of natural magnesite is a feasible technology that can attain a 100% removal efficiency by fully making profit of the magnesium enhancement effect.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the most conventional method to reduce SO 2 emissions is to operate flue gas desulfurization (FGD) devices (Xu 2011), However, FGD operations have many disadvantages, such as high cost, poor byproduct quality, and secondary pollution . For instance, Wet limestone FGD processes are extensively used at point sources which accounts for over 90 % of installed desulfurization capacities in the world (Kikkawa et al 2002), but such process is not environment friendly enough because 1 M CO 2 is released along with 1 M SO 2 adsorption (Gutiérrez Ortiz et al 2006;Michalski 2006). According to the data over 2005-2010, the contribution weight of engineering technology for reduction of SO 2 was 62.71 % (Tursun et al 2015), which means that some cleaner and greener technologies for flue gas desulfurization are of great importance to develop.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies explore the influence of some specific compounds on SO 2 capture efficiency such as chloride content, , magnesium content, addition of organic additives, or the influence of a specific limiting step such as limestone reactivity , or sulfite oxidation. …”
Section: Introductionmentioning
confidence: 99%
“…Gypsum precipitation has been experimentally studied, 22,23 and population balances can be used to quantify the complex behavior of crystal nucleation and growth in the suspension. 24 Industrial & Engineering Chemistry Research ARTICLE Numerous studies explore the influence of some specific compounds on SO 2 capture efficiency such as chloride content, 25,26 magnesium content, 27 addition of organic additives, 28À30 or the influence of a specific limiting step such as limestone reactivity 21,31À36 or sulfite oxidation. 37À41 Some other studies focus on the aero-and hydrodynamics of FGD units 42,43 in order to determine pressure drop, gas misdistribution, and droplet coalescence or to link desulfurization efficiency with these phenomena.…”
Section: Introductionmentioning
confidence: 99%